Effects of Dietary Indole-3-carboxaldehyde Supplementation on Growth Performance, Intestinal Epithelial Function, and Intestinal Microbial Composition in Weaned Piglets - Zhang, Ruofan; Huang, Guowen; Ren, Yuting; Wang, Haifeng; Ye, Yanxin; Guo, Jiaqing; Wang, Mengting; Zhu, Weiyun; Yu, Kaifan (Frontiers in Nutrition, 2022)
As a microbial tryptophan metabolite, indole-3-carboxaldehyde (ICA) has been suggested to confer benefits to host, such as regulation of intestinal barrier function. This study aimed to elucidate the role of ICA in modulating intestinal homeostasis via using a weaned pig model. Twenty-four weaned piglets were randomly allocated into three groups: the control group (a basal diet), ICA100 group (the basal diet supplemented with 100 mg/kg ICA), and ICA200 group (the basal diet supplemented with 200 mg/kg ICA). The experiment lasted 14 d, and pigs from the control and ICA100 groups were slaughtered. The results showed no significant differences in the average daily gain (ADG) and average daily feed intake (ADFI) among the three groups (P > 0.05). However, the ICA100 group had a lower feed to gain ratio (F:G) (P < 0.05). Dietary ICA supplementation did not alter the villus height, crypt depth, and villus height/crypt depth ratio in the small intestine, and did not change the intestinal permeability and antioxidant parameters (P > 0.05). Intriguingly, ICA treatment significantly increased the jejunal, ileal and colonic indexes in piglets (P < 0.05). Besides, the expression of proliferating cell nuclear antigen (PCNA) in the intestine was up-regulated by ICA treatment. Moreover, in vitro experiments demonstrated that 15 μM ICA significantly accelerated the proliferation activity of IPEC-J2 cells, and increased the expression of the ICA receptor aryl hydrocarbon receptor (AHR) and the proliferation markers PCNA and Cyclin D1 (P < 0.05). In addition, dietary ICA supplementation modulated the intestinal flora, increasing the richness estimators and diversity index, decreasing the abundances of phylum Fibrobacterota and genera Alloprevotella, Prevotella, and Parabacteroides, and enriching the abundance of genera Butyrivibrio. These data reveal a beneficial role for the microbial metabolite ICA on intestinal epithelial proliferation, rather than intestinal barrier function, in weaned piglets.